Penerapan Etika Bisnis Islam pada Jasa Barbershop di Kabupaten Magelang - Saputra, Ahmad Ghulami Adyan Danar; Purwanto; Kholidah, Nur; Labib, Achmad (Forum Kerjasama Pendidikan Tinggi, 2023)
In the era of globalization and modernization, the barbershop business not only focuses on aesthetic aspects but also develops as a place that offers a holistic experience to customers. In this context, it is crucial to assess the extent to which the principles of Islamic business ethics are applied in Barbershop operations, especially in Magelang Regency, which is known to have a diverse society and strong cultural values. This research aims to determine the application of Islamic business ethics to the barbershop business. This research was written using a descriptive qualitative approach to find out the Islamic view of applying business ethics and how to apply Islamic business ethics to increase customer satisfaction. The objects taken in this research were three Barbershop businesses in Magelang Regency. The data used in this research is primary data obtained from interviews with Barbershop leaders and customer representatives. The research data was tested for data validity using source triangulation. Research data was collected using interviews and observation. Research data was analyzed by applying the interactive model developed by Miles and Huberman. The results of this research indicate that the Barbershop business has implemented the principles of Islamic business ethics in the form of unity (tauhid), the principle of balance, the principle of free will, the principle of responsibility, and the principle of virtue (ihsan). This research also provides information that applies Islamic business ethics values ​​in barbershops, creates professional service, and develops close emotional relationships with customers. The implications of these findings include the potential for increased customer satisfaction, which is a critical aspect of a business's long-term growth and success.